(3ELQGAGJ GdJbGVi CeGe GdeMGce GdYeGdjI (B: s (3OQGSI ebGQfI (B/ s - (3YHO GdEdg RHjQGJs; (3CMeO MSf GdHQYi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3egeG HdZJ GdMeGjI h GdMbhb h GdVeGfGJ GdebQQI ai GdbhGfjf GdGLJeGYjI HUaI YGeI(B: (3h egeG HdZJ GdecJSHGJ GdJi MbbJgG GdWHbI GdYeGdjI Ydi eSJhi GdbhGfjf GdGLJeGYjI GdehVhYjI(B: (3aSjHbi Pdc YHKG(B: (3EPG de jcf gfGc JfXje bVGFi bGOQ Ydi fbd Jdc GdMeGjI h GdVeGfGJ h GdMbhb ef MGdI GdSchf Edi MGdI GdMQcI(B: (3h Pdc Yf WQjb GdLHQ YfO GdeS HgG Ch NQbgG(B. (3h GdbVGA GdYeGdj HgPg GdeKGHI ShGA cbhGYO ELQGFjI efXeI deSWQI GbJVGA GdMb(B: (3Ch cCWQ bVGFjI Ci cQCSeGd KbGai egfi(B: (3jeKdGf Cge hSGFd YOGdI GdYed dJMbjb CZQGV GdJTQjY GdGLJeGYi(B: (3h CgOGa YGde GdYed YeheG(B: (3h ai ebOeI Jdc GdCgOGa OYe GSJbQGQ QhGHW GdYed h OYe GdCLQ GdbGQ(B: (3h eG jSJJHY Pdc ef Sde GLJeGYi OGNd GdefTCI(B: (3dg GfYcGSGJg GdYGeI Ydi GdEfJGL h GdMjGI GdGbJUGOjI h GdGLJeGYjI YeheG(B: (3h Gdcd ai EWGQ CHYGOg h GQJHGWGJg GdYGeI(B. (3h Ydi gPG GdCSGS abO GfWdJ GdOQGSI h GdHMK ai gPg GdCWQhMI ef ETcGdjI YejbI JJeKd ai acQI gd GdeYfjjf h GdeJJHYjf h GdegJejf HYOGdI GdYed ai hVY GWeFfGf Ydi SjQ OhGdjH GdbVGA GdYeGdi(B: (3HGYJHGQg GdedLC GdChd h GdCNjQ(B: (3GdVGef ddQbGHI Ydi MSf JWHjb ebJVjGJ bGfhf GdYed(B: (3h GdbhGfjf GdJi JOhQ ai adcg(B: (3GdPi JfXQ efg GdWHbI GdYGedI GdfXQ ai efGRYGJgG GdYeGdjI(B: (3Ydi hLg GdSQYI h CfLY JfajP(B: (3h HCbd JcdaI(B: (3OYeG ddCLQ h GdYed GdbGQ(B: (3h TQYjI JWHjb ebJVjGJ JTQjYGJ GdYed ccd(B. (3h ddELGHI Ydi gPg GdETcGdjI SdcJ ai gPg GdCWQhMI efgLG YdejG JMdjdjG h hGbYjG(B: (3eSJYjf ai Pdc HGdCfXeI GdbGfhfjI ai cd ef eUQ h GdeZQH h aQfSG(B: (3MjK bSeJ gPg GdCWQhMI Edi HGHjf JfGhdJ ai GdHGH GdChd ehVhY GdeMGce GdYeGdjI GdJfXje h GdGNJUGUs
(3jTJed Ydi edGMb(B: (3UaMGJ (B200-227s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdELJeGYjI, (B2021s
(3HHdjhLQGajG(B: (3UaMGJ (B228-236s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GdJfXje GdbVGFi ddeMGce GdYeGdjIs; (3GNJUGU GdeMGce GdYeGdjIs; (3GLQGAGJ GdeMGce GdYeGdjIs; (3Mce GdeMGce GdYeGdjIs; (3GdeMGce GdYeGdjIs; (3GdJTQjY GdeZQHis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs